Understanding the Mental Health Impacts of Climate Change in South Africa: Qualitative Insights From Researchers, Practitioners, Ethicists, and Funders on the Need for a Transdisciplinary Approach - Andrew Tomita; Princess Nyoni; Joyce Mlay; Jessica Garlick; Rosebub Gugulethu Gcaba; Thobile Maphumulo; Helga Chauke; Richard Lessells; Admire Nyamwanza (Health Science Reports, 2026)
ABSTRACT Background Against a backdrop of entrenched structural inequalities, poverty, and limited healthcare resources, climate change represents a major public health challenge in South Africa, with significant yet under‐recognized consequences for mental health. Expert perspectives on these impacts remain limited, highlighting a critical gap in informing transdisciplinary responses. Objectives To explore stakeholder perspectives (researchers/academics, research ethics committee members, employees of organization that funds climate or health research) on transdisciplinary responses to the mental health impacts of climate change in South Africa. Methods This exploratory qualitative study examined expert perspectives on the mental health impacts of climate change. Twelve purposively sampled stakeholders participated in in‐depth semi‐structured interviews. Data collection continued until data saturation was reached ( n = 12). Data were analyzed using an inductive thematic approach. Findings Three overarching themes were identified. First, direct mental health impacts included anxiety, depression, trauma, and exacerbation of pre‐existing conditions, with links to severe mental illness, including climate‐related delusional symptoms and increased substance use. Second, indirect pathways included socioeconomic vulnerability, community resilience, and the dual role of media in raising awareness and contributing to psychological distress. Third, participants emphasized the need for strengthened transdisciplinary approaches. Conclusions Addressing mental health impacts of climate change requires integrated, contextually relevant, transdisciplinary interventions to strengthen resilience among vulnerable communities.